European extraterritoriality on semicolonial Ethiopia - Hailegabriel G FEYISSA (Melbourne journal of international law, 2016)
Ethiopia's experience with European legal imperialism - European extraterritoriality in Ethiopia - weak during the first third of the 20th century - reached its zenith in the post-Second World War period - was miscast as a modernisation project, rather than a colonial one.